Functional cloning of a gp100‐reactive T‐cell receptor from vitiligo patient skin. (4th March 2016) - Klarquist, Jared; Eby, Jonathan M.; Henning, Steven W.; Li, Mingli; Wainwright, Derek A.; Westerhof, Wiete; Luiten, Rosalie M.; Nishimura, Michael I.; Le Poole, I Caroline
Summary: We isolated gp100‐reactive T cells from perilesional skin of a patient with progressive vitiligo with superior reactivity toward melanoma cells compared with tumor‐infiltrating lymphocytes 1520, a melanoma‐derived T‐cell line reactive with the same cognate peptide. After dimer enrichment and limited dilution cloning, amplified cells were subjected to reverse transcription and 5′ RACE to identify the variable TCR α and TCR β subunit sequences. The full‐length sequence was cloned into a retroviral vector separating both subunits by a P2A slippage sequence and introduced into Jurkat cells and primary T cells. Cytokine secreted by transduced cells in response to cognate peptide and gp100‐expressing targets signifies that we have successfully cloned a gp100‐reactive T‐cell receptor from actively depigmenting skin.